Analisis Risiko Bahaya Kecelakaan Kerja Dan Pengendalian Bahaya Dengan Pendekatan Hazard Identification, Risk Assessment And Risk Control (Hirarc) Pada UMKM Rosabonita Bakery - Emmy Nurhayati; Dyah Ari Susanti; VRB Kurniawan (Univesitas PGRI Yogyakarta, 2021)
Micro, Small and Medium Enterprises (MSMEs) Rosabonita Bakery is one of the small businesses in the bakery sector. UMKM Rosabonita Bakery accepts orders for making wet and dry cakes both individually and in large parties. MSME Rosabonita Bakery is located in Gumpang, Kartasura, Sukoharjo, Central Java. This is still done independently by the owner and the production site has not been designed professionally because it is still at home so there will be many hazards that can endanger safety at work. Based on observations in the Rosabonita Bakery production area, there are several Important Potential Hazards that need to be identified. This needs to be done in order to create an ideal Occupational Health and Safety in the workplace and also increase productivity. The results of this study are expected that Rosabonita Bakery SMEs can use the Hierarchy of Control in controlling the potential hazards that exist so that work accidents can be minimized.